2023
DOI: 10.1042/bst20221067
|View full text |Cite
|
Sign up to set email alerts
|

Viral subversion of the cell polarity regulator Scribble

Abstract: Scribble is a scaffolding protein that regulates key events such as cell polarity, tumorigenesis and neuronal signalling. Scribble belongs to the LAP family which comprise of 16 Leucine Rich Repeats (LRR) at the N-terminus, two LAP Specific Domains (LAPSD) and four PSD-95/Discs-large/ZO-1 (PDZ) domains at the C-terminus. The four PDZ domains have been shown to be key for a range of protein–protein interactions and have been identified to be crucial mediators for the vast majority of Scribble interactions, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Our identification of Scrib as a potential partner of the SARS-CoV-2 E protein adds this protein to the large list of viral proteins that interact with this adaptor molecule that facilitates key molecular interactions at distinctive subcellular regions [ 33 ]. Scrib belongs to the LAP (LRR and PDZ) family; it contains 16 Leucine Rich Repeats (LRR), two LAP-specific regions and four PDZ domains.…”
Section: Resultsmentioning
confidence: 99%
“…Our identification of Scrib as a potential partner of the SARS-CoV-2 E protein adds this protein to the large list of viral proteins that interact with this adaptor molecule that facilitates key molecular interactions at distinctive subcellular regions [ 33 ]. Scrib belongs to the LAP (LRR and PDZ) family; it contains 16 Leucine Rich Repeats (LRR), two LAP-specific regions and four PDZ domains.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, SseM is unique among Salmonella effectors in containing a functional PBM and as a bacterial protein targeting the DAPC. Several viral oncoproteins target DLG1 to regulate viral virulence [39, 40]. It therefore now essential to investigate the biochemical consequences and physiological significance of SseM’s interaction with DLG1 and DAPC components.…”
Section: Discussionmentioning
confidence: 99%
“…SseM_5 [50] SseM_6_pseudo [40] SseM_7 [24] SseM_8 [20] SseM_9 [18] SseM_10 [14] SseM_11_pseudo [14] SseM_12 [13] SseM_13 [12] SseM_14 [11] SseM_15 [10] SseM_16 [10] SseM_17 [8] SseM_18 [8] SseM_19_pseudo [7] SseM_20 [7] SseM_21_pseudo [7] SseM_22 [7] SseM_23 [7] SseM_24 [6] SseM_25_pseudo [6] SseM_26 [6] SseM_27_pseudo [5] SseM_28 [5] SseM_29 [4] SseM_30 [4] Others [81] Missing [2] SseM variants…”
Section: Figures Andmentioning
confidence: 99%
“…The N-terminal PTB structural domain of CAPON can bind and function with multiple proteins, such as Scribble, the Synapsin family (including Synapsin I, Synapsin II, and Synapsin III), and Dexras1 [30]. Scribble is a cell polarity protein that is present in the pre-synaptic and post-synaptic membranes [63,64], and it exists as a scaffolding protein. Scribble directly connects with CAPON without the assistance of other proteins.…”
Section: The N-terminal Ptb Structural Domain Of Capon Binds To a Var...mentioning
confidence: 99%
“…Thus, it can be concluded that CAPON is essential for synapse growth in mammals [48]. In addition, Scribble plays a role in cell polarity, differentiation, and migration [37,64,66]. It also functions in tumorigenesis inhibition, and it can bind with Yes-associated protein (YAP) and connect with CAPON to form a triplet complex CAPON-Scribble-YAP [67] (Figure 3).…”
Section: The N-terminal Ptb Structural Domain Of Capon Binds To a Var...mentioning
confidence: 99%